Household waste management practices of barangay Dagsian, Baguio City - Angalao, Lovelyn L.
The focus of this study is the household waste management of barangay Dagsian in relation to several themes. A survey was conducted to find out household waste generation but personal interviews with key informants were employed to gain an in-depth understanding or community concerns. Household waste management is seen in connection to factors such s years of residence, house ownership, age, educational attainment, source of income, income, number of family members and sex. The factors in waste management are seen to affect community waste management behavior and individual households' agency. As a general observation, the importance of the idea of waste construction surfaced in the study. The practice of plastic production was easily observed to be a general trend in the barangay. Waste in not really a problem since the community members perceive that the officials are doing their job properly. This is connected to the dependence on authorities. Now, there were important findings that were shown concerning the factors that influence waste management. House owners, women, large families, long-term and older residents, participants with high educational attainments, formal workers, and high-therefore recommended that the waste management of these groups would be enhance through barangay programs. On the other hand, those in the opposite categories are seen as the focus of waste management seminars -- Author's abstract.